Accelerometry: A feasible method to monitor physical activity during sub-acute rehabilitation of persons with stroke - Conran Joseph; Björn Strömbäck; Maria Hagströmer; David Conradsson (Medical Journals Sweden, 2018)
Objective: To investigate the feasibility of using accelerometers to monitor physical activity in persons with stroke admitted to inpatient rehabilitation. Design: Longitudinal observational study. Participants: Persons with stroke admitted to a specialized rehabilitation centre for sub-acute rehabilitation were recruited between August and December 2016. Methods: Volume and intensity of physical activity were assessed with accelerometers throughout the rehabilitation period. Indicators of feasibility included processes (recruitment, protocol adherence and participants' experiences) and scientific feasibility, which assessed the accelerometers' ability to detect change in physical activity among stroke survivors who ambulate independently and those who are dependent on a mobility device. Results: Twenty-seven out of 31 eligible individuals took part in this study, with 23 (85%) completing it. In total, 432 days of rehabilitation were monitored and valid physical activity data were obtained for 408 days (94%). There were no indications that the measurement interfered with participants' ability to participate in rehabilitation. Despite the subjects' ambulation status, the number of steps and time spent in moderate-to-vigorous physical activity increased significantly across the first 18 days of rehabilitation, whereas sedentary time was unchanged. Conclusion: This study supports the feasibility of using accelerometers to capture physical activity behaviour in survivors of stroke during inpatient rehabilitation.